L’affirmation de l’exemplarité environnementale comme stratégie de métropolisation des villes nordiques - Camille Girault (EchoGéo)
Northern European cities are often considered by many stakeholders as urban sustainability models. Their environmental ambitions and performances strongly feed the construction of the urban Nordic model and its different versions. For cities characterized by some European and world periphericity, the assertion of such an environmental exemplarity actually contributes to a metropolitan integration wish in Europe and in the world. Consequently, this paper aims to analyze the relationship between the metropolitan processes and the production of the Nordic model of urban sustainability. By developing a model of urban sustainability which is environmentally centered in order to assert themselves in a globalized and competitive context, the different urban stakeholders actually implement a shared strategy of metropolization.